2018
DOI: 10.1155/2018/2606834
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Contributes to Drug Resistance of NK/T-Cell Lymphoma Cells by Regulating ABCC4

Abstract: Background Extranodal natural killer/T (NK/T) cell lymphoma, nasal type (ENKTL), represents a rare subtype of T-cell lymphomas with aggressive clinical behavior and is relatively resistant to chemotherapy. However, there is relatively poor understanding of molecular pathogenesis of multidrug resistance in ENKTL. Here, we aimed to explore the biological roles and potential mechanism of IL-13 and ABCC4 in multidrug resistance of NK/T-cell lymphoma. Methods ELISA analysis was used to determine the level of serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Secretion of IL-4 and IL-10 by cancer cells has been shown to confer drug-induced resistance, by specifically inhibiting apoptotic pathways (87)(88)(89). IL-13 has also been shown to promote drug resistance in lymphoma, although the mechanism is unclear (90). These cytokines can thus be useful as predictive biomarkers, and to monitor resistance towards anticancer drugs.…”
Section: Cytokines Induced Due To Therapy and Resistance To Therapymentioning
confidence: 99%
“…Secretion of IL-4 and IL-10 by cancer cells has been shown to confer drug-induced resistance, by specifically inhibiting apoptotic pathways (87)(88)(89). IL-13 has also been shown to promote drug resistance in lymphoma, although the mechanism is unclear (90). These cytokines can thus be useful as predictive biomarkers, and to monitor resistance towards anticancer drugs.…”
Section: Cytokines Induced Due To Therapy and Resistance To Therapymentioning
confidence: 99%
“…Response rates of MDR1 -negative subjects to CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) is significantly higher than those MDR1 -positive in 1 study but not others [ 90 ]. Interleukin-13 (IL-13) and ABCC4 are highly expressed in NKTLs and also contributes to doxorubicin resistance [ 91 ]. Wang et al reported a higher concentration of IL-2 receptors α (IL-2R α) on NKTL cell lines compared with normal NK-cells [ 92 ].…”
Section: What Is the Mechanism Of Multi-drug Resistance (Mdr) In Nktl?mentioning
confidence: 99%
“…Based on gene expression regulation technology, overexpression of ABCC4 and ABCG4 can induce epirubicin (EPI) and cisplatin (DDP) resistance in human NK/ T cell lymphoma YTS cells and reduce cell apoptosis [ 72 ]. Meanwhile,IL-6, IL-10, and IL13 mediate ABCC4 resistance in T-cell lymphoma [ 64 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%